Antigenic cell associated Dengue 2 Virus proteins detected in Vitro using Dengue fever patients Sera - AbuBakar, Sazaly; Azmi, A.; Misbah, S.; Chang, L.Y. (2002)
At least three major antigenic dengue 2 virus proteins were recognized by pooled dengue fever patients' sera in infected Aedes albopictus (C6/36) mosquito cells. Dengue virus envelope (E), premembrane (PrM) and non-structural protein 1 (NS 1) dimer were detected beginning on day 3 postinfection in both the cell membrane and cytosolic fractions. Using the patients' sera, the presence of antigenic intermediate core protein (C)-PrM and NS1-non-structural protein 2a (NS2a) in the cytoplasmic fraction of dengue 2 virus infected cells was revealed. The presence of a approximately 92 and approximately 84 kDa NS 1 dimer in the membrane (NS 1m) and cytosolic (NS 1c) fractions of C6/36 cells, respectively, was also recognized. Using individual patient's serum, it was further confirmed that all patients' sera contained antibodies that specifically recognized E, NS 1 and PrM present in the dengue 2 virus-infected cell membrane fractions, suggesting that these glycosylated virus proteins were the main antigenic proteins recognized in vivo. Detection of dengue 2 virus C antibody in some patients further suggested that C could be antigenic if presented in vivo.